A Phenomenological Study to Assess the Lived Experiences of Parents of Children with Congenital Disorders Admitted in Paediatric Health Care Settings of Selected Paediatric Hosp - P. Joseph, Rajesh; E.V. , Nirmal Raj; Belagavi, Dayanand; Christian, Carol; Baria, Bhanu; Ilesh, Joshi; Ragini, Bhoi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Congenital anomalies have been understood as a root cause for neonatal morbidity and mortality in recent days. Living with a congenital anomaly is a critical issue, and that might influence diverse aspects of a parent’s life. It is a burden for the parents to deal with the hospitalization and activities of daily living of the children. Aim: The investigators aimed to illustrate the lived experiences of parents having children with congenital anomalies. Material and Methods: A qualitative study was carried out using the phenomenological hermeneutical method to transcribe the lived experiences of the parents having children diagnosed with any form of congenital anomaly. Twenty-five mothers were identified from three pediatric hospitals by convenience sampling technique and interviewed by using an open-ended questionnaire. Each interview was audio recorded and lasted for 30 to 45 minutes. The narrated experiences were interpreted into a meaningful statement for exploration. The analysis of collected information led to the development of themes. Results: The present study helped us to highlight the emotions, feelings, and challenges of parents dealing with children during their hospitalization. Socio-demographic characteristics showed that the majority (84%) of the parents were mothers. The interview verbatim was transcribed into seven themes for deeper understanding. (1) Emotional experiences, (2) experiences related to financial issues, (3) experiences concerned with social perspectives, (4) child-centered experiences, (5) experiences on knowledge and awareness, (6) child self-care experiences (7) experiences towards exposure to unfamiliar environments. Conclusion: The study insists on the importance of routine assessments to be conducted by the health care providers to understand the strange experiences of parents during their child’s hospitalization. The support they receive through health care and therapeutic interpersonal relationships would promote the physical and psychological well-being of parents.